A Critique of Alexy's Claim to Correctness. (10th June 2020) - Bix, Brian H.
Abstract: This article offers an overview of the difficulties in Robert Alexy's idea of law's "claim to correctness." The inquiry takes us deep into the nature of simple communication, back out to what it means to have a theory about the nature of law, and also in the direction of wondering about the interaction of legal theory and practical reasoning—reasoning about how we should best act. The article offers reasons to question whether law in fact makes claims, at least in any straightforward sense. Even if one brackets that matter, there are reasons to raise doubts about what is in fact implicit in the act of lawmaking. At one level, an act of lawmaking does implicitly assert the authority to act in that way. Whether it also implies that the content of the action is morally good, or at least not clearly morally bad, is, at a minimum, a harder question.